The Accuracy of Press Reports Regarding the Foreign Exchange Interventions of the Bank of Japan - Michael Frenkel; Christian Pierdzioch; Georg Stadtmann (Kiel Institute of World Economics (IfW), 2002)
This paper presents evidence on the accuracy of press reports regarding the foreign exchange market interventions conducted by the Bank of Japan (BoJ) between January 1995 and December 1999. We find that the reports of interventions in the financial press are a relatively inaccurate indicator for the actual interventions of the BoJ. We also find that the accuracy of press reports of BoJ interventions is higher for those interventions which were carried out jointly by the BoJ and the Federal Reserve.
Keywords: F31; G14; G15; F33; 330; Foreign exchange market; Central bank interventions; Press reports of interventions; Bank of Japan; Wechselkurspolitik; Staatliche Information; Wirtschaftsinformation; Monetärer Indikator; Schätzung; Japan